Trust works! : four keys to building lasting relationships - Blanchard, Kenneth H.; Olmstead, Cynthia; Lawrence, Martha C. (New York : William Morrow, 2013)
Offers advice for building and maintaining trust in order to improve interpersonal harmony and cooperation, and thus create a more productive and healthy work environment or social group.
Keywords: Trust; Interpersonal relations; Interpersonal Relations; Trust